Fertility preservation by ovarian tissue cryopreservation of children in China——umbilical single-incision surgery and perioperative experience - Qipeng, Zheng; Jing, Liu; Yun, Su; Zexi, Li; Zhenhua, Cao; Meng, Chen; Yan, Zhou; Hua, Zhang; Zecheng, Wang; Yu, Tian; Xiangyan, Ruan; Yurui, Wu (Frontiers in Endocrinology, 2025)
BackgroundOvarian tissue cryopreservation and transplantation (OTCT) is an effective method for preserving fertility and endocrine function. This study aims to summarize the surgical techniques and perioperative experiences to provide clinical evidence for pediatric OTCT.MethodsThis retrospective study reviewed the clinical data of 89 children who underwent umbilical single-incision laparoscopic oophorectomy at Children’s Hospital, Capital Institute of Pediatrics between September 2020 and December 2024. The types of primary diseases were summarized, differences in preoperative complete blood count results, surgery methods and intraoperative conditions were explored among different primary diseases. Different surgical methods were reviewed. The surgery steps and techniques were summarized. The trends in surgical volume over time and the surgical learning curve were analyzed. The factors affecting follicle density were also explored.ResultsThe primary diseases in this study included Turner syndrome, aplastic anemia, mucopolysaccharidosis in, chronic active Epstein-Barr virus (EBV) infection, hematological malignancies, solid tumors, platelet dysfuction, metachromatic leukodystrophy, hemophagocytic syndrome, myelodysplastic syndrome, beta-thalassemia, osteopetrosis, dermatomyositis, congenital dyserythropoietic anemia, metachromatic leukodystrophy, and primary immunodeficiency. Children received chemotherapy will experience a decrease in white blood cell (WBC) and neutrophil levels, necessitating granulocyte-stimulating therapy; children with aplastic anemia had a significant drop in hemoglobin level, thus requiring red blood cell transfusions; children with myelodysplastic syndrome and aplastic anemia showed a marked decrease in platelet levels, necessitating platelet transfusions. Children with Turner syndrome most commonly have the unclosed internal inguinal ring. The main steps of umbilical single-incision laparoscopic oophorectomy were incision, trocar placement, observation, suspension, dissection, removal, and incision closure. The number of umbilical single-incision laparoscopic oophorectomy had been increasing year by year. The learning curve analysis indicated that the first 35 cases were the learning and improvement phase. Follicular density was significantly correlated with age, primary disease and ovarian color.ConclusionPediatric OTCT has broad applications and a promising future. Perioperative preparation and the surgical process are important. It is necessary to adjust the complete blood cell count to ensure that WBC greater than 4*10^9/L, neutrophils greater than 1*10^9/L, hemoglobin greater than 70 g/L, and platelet greater than 100*10^9/L before surgery. Given the small volume of children’s ovaries, it’s necessary to remove the entire ovary. Energy devices can be utilized, however, it’s essential to minimize mechanical, thermal damage, and warm ischemia time to the ovary, while also preserving surrounding tissues.